În căutarea românului perfect. Specific național, degenerare rasială și selecție socială în România modernă. Iași, Editura Polirom, 2024. Marius Turda - Adrian-Nicolae Furtună (Sociologie Românească)
Through In Search for the Perfect Romanian. National Specificity, Racial Degeneration and Social Selection in Modern Romania [În căutarea românului perfect. Specific național, degenerare rasială și selecție socială în România modernă], Marius Turda proposes a new method to understand and explain the foundations of Romanian nationalism between 1880 and 1950. Structured in six chapters, the book shows that in Romania there was a eugenic and biopolitical culture that was to define Romanian nationalism and scientific racism. Its extreme forms materialized in the measures taken against Jews and Roma during the Holocaust in Romania. I review the book from the perspective of social memory. By questioning some present-day commemorative practices I highlight the present legacies of eugenics: schools named after strategists of racism, such as Sabin Manuilă; public commemorations of anti-Semites such as Liviu Stan or Nicolae Paulescu.